2008
DOI: 10.1515/jpm.2008.001
|View full text |Cite
|
Sign up to set email alerts
|

The roles of long-chain polyunsaturated fatty acids in pregnancy, lactation and infancy: review of current knowledge and consensus recommendations

Abstract: This paper reviews current knowledge on the role of the long-chain polyunsaturated fatty acids (LC-PUFA), docosahexaenoic acid (DHA, C22:6n-3) and arachidonic acid (AA,, in maternal and term infant nutrition as well as infant development. Consensus recommendations and practice guidelines for health-care providers supported by the World Association of Perinatal Medicine, the Early Nutrition Academy, and the Child Health Foundation are provided. The fetus and neonate should receive LC-PUFA in amounts sufficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
434
1
41

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 588 publications
(485 citation statements)
references
References 77 publications
9
434
1
41
Order By: Relevance
“…This suggests that higher DHA intake may influence its content in human milk, especially during the first weeks after delivery. This result is in agreement with those of other studies that demonstrated the positive influence of omega-3 supplementation on the milk of mothers taking such supplements 1,17,21,28,30 . Lauritzen et al 44 also observed an increase in the omega-3 content of human milk after fish oil supplementation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This suggests that higher DHA intake may influence its content in human milk, especially during the first weeks after delivery. This result is in agreement with those of other studies that demonstrated the positive influence of omega-3 supplementation on the milk of mothers taking such supplements 1,17,21,28,30 . Lauritzen et al 44 also observed an increase in the omega-3 content of human milk after fish oil supplementation.…”
Section: Discussionsupporting
confidence: 93%
“…The fat profile found for the CG were similar to those found by Silva et al 39 , Cunha et al 40 and Patin et al 21 , while studying the fat profile of the milk of Brazilian women, including EPA and DHA. Trans fatty acids were also found by Kolelzko et al 17 and by authors of other countries whose results were discussed by Costa & Sabarense 24 .…”
Section: Discussionsupporting
confidence: 67%
“…Variation of dietary intake plays a key role in reducing some risks associated with pregnancy, such as risk of fetal and infant mortality, low birth weight [12,13] and premature births [2]. In this study, we observed that vaginally administered DHA during pregnancy acts on uterine contractions, in symptomatic women resulting in muscle relaxation and induces disappearance of spontaneous contractions in many cases.…”
Section: Discussionmentioning
confidence: 77%
“…Several randomized controlled trials have shown that supplementation with omega-3 may influence the birth process by delaying the onset of labor, reducing the risk of recurrent preterm birth and in animal studies it seems to have a tocolytic effect [2,15]. The exact DHA's mechanisms of action are not well understood, the eicosanoid-mediated changes on myometrial contractions and the connective tissue remodeling [5,12,15] seem involved. A high omega-6/omega-3 fatty acid ratio will result in increasing proinflammatory eicosanoid production; these metabolites have been associated with labor at term and preterm.…”
Section: Discussionmentioning
confidence: 99%
“…Fish is also the main source for n-3 PUFA; these nutrients are important in the maternal diet during pregnancy and lactation (19) . These elongated fatty acids include DHA and EPA, which are essential for optimal neural tissue development and function (20) .…”
mentioning
confidence: 99%